Evaluation of Root Canal Morphology of Maxillary First Premolars by Cone Beam Computed Tomography in Saudi Arabian Southern Region Subpopulation: An In Vitro Study - Shadia Maghfuri; Husain Keylani; Hitesh Chohan; Salha Dakkam; Aeshah Atiah; Mohammed Mashyakhy (International Journal of Dentistry)
Introduction. The aim of this study was to investigate the root canal morphology of maxillary first premolars in Saudi Arabian subpopulation by cone beam computed tomography (CBCT). Methods. One hundred maxillary first premolars were collected from the College of Dentistry at Jazan University and different dental centers in the southern region of Saudi Arabia. These teeth were cleaned thoroughly and were mounted in a plastic artificial mandible jaw to mimic soft tissue which was then placed in a water container. The 3D scan images were obtained with CBCT imaging (3D Accuitomo170) and evaluated on the basis of the number of roots, number of canals, and root canal configuration using Vertucci’s classification. Results. Out of the 100 maxillary first premolars, the majority of teeth had 2 roots (61%) followed by (36%) one root. Two canals were the most predominant with 97% and then 3% three canals, and no tooth presented with one canal. Type IV canal configuration was most prevalent (75%) followed by Type V (13%). Conclusions. The CBCT provides enhanced and accurate information of root morphology, canal configuration, and its variations, thereby constituting an excellent alternative for radiographic diagnosis tool in the dental practice.